A nagykamarási avar kori temetőrészlet - Sajti Marianna Adrienn (2021)
On August 16–28, 1926, János Banner carried out a rescue excavation in Nagykamarás (today Békés County, Hungary), in the course of which 27 Avar burials were unearthed. Banner was only able to save a part of the cemetery and there were lots of stray finds. In the cemetery part, the NW-SE orientation dominated. The dead were placed in the grave pit in an extended position and in one case in a contracted position (grave 22). Most of the burials were shaft graves, in one case there was a niche dug from the end of the grave pit (grave 17). The looting of the graves was observed in three cases (graves 8, 10, 18). Two deceased persons were certainly buried in coffins (grave 5, 15), however, twisting into a shroud or the use of a narrow-carved coffin cannot be ruled out (graves 12, 17). At several burials, the excavator also recorded food offerings (graves 12, 18) and animal sacrifices (graves 5, 17, 18). In addition, burials without grave goods also came to light (graves 22, 23). In many cases, grave goods and items of clothing and wear were identifiable. The deceased of grave 7 stands out of the male burials with his costume and accessories: silver belt set, horse equipment, poleaxe, and knife. Among the female burials, the skeleton of grave 4 with pearl earrings, grave 17 with its silver earrings and glass beads ornament, and a bronze bracelet found in grave 9 can be highlighted. According to recent data, 13 women, 11 men, 2 children and 1 adult skeleton were unearthed during the excavation. The cemetery can be dated to the last third of the 7th century – 8th century.
Keywords: Bölcsészettudományok; Történettudomány és régészet